Why Do the Earnings of Male and Female Graduates Diverge? The Role of Motherhood and Job Dynamics - Aedin Doris; Donal O'Neill; Olive Sweetman (Institute of Labor Economics (IZA), 2022)
This paper explores gender wage dynamics using an administrative dataset covering Irish graduate earnings from 2010-2020. Our data allows us to look at a broad range of degrees and compare workers who are identical in important observable characteristics. We find that although male and female graduates have similar returns to study field immediately after graduation, a substantial gap soon emerges. This is particularly true when considering women with children and is driven by a 27 percent fall in earnings immediately after childbirth. We find no striking differences between fields of study; there is a substantial and persistent motherhood effect for all field groupings. We examine and dismiss the possibility that the gender difference in earnings dynamics is driven by job mobility; in fact, almost all of the difference is accounted for by changes within a job. Although there is a large and persistent reduction in hours of work after childbirth, this does not seem to explain all of the reduction in earnings.
Keywords: J01; 330; motehrhood penalty; gender pay gap; field of study